(3Yde JObjb GdMSGHGJ (B/s - (3GdMOQH, RgjQs ((3YeGf(B: s (3OGQ GdHOGjI(B, s, 2010)
(3JYQja GdJObjb h CfhGYg , GdGNWGA h GdZT , bhGYO GdJObjb h bhGYO GdSdhc Gdegfj h JbQjQ GdeObb h eObb GdMSGHGJ , GdGKHGJ aj GdJObjb h GLQGAGJ JfajP YedjI GdJObjb , GdQbGHI GdOGNdjI h JObjb GdCUhd GdeJOGhdI h WhjdI GdGLd , JObjb GdGdJRGeGJ bUjQI h WhjdI GdCLd h Mbhb GdedcjI , JObjb Mbhb GdedcjI h GdeNUUGJ GdGMJjGWjI h GdCQUOI GdOGFfI GdCNQis
Keywords: (3GdeMGSHIs; (3eQGLYI GdMSGHGJs